Advanced call logging for public safety organizations. - Procops, Tony (Public Management (00333611), 2000)
The more advanced technological features of the most up-to-date call-logging equipment are essential for saving lives, offering legal protection, and improving interaction with the public. Selective and bulk recording are now integrated into the latest systems, meaning that there is no longer a need for separate hardware, and equipment can now provide services that were previously unavailable. Advance call logging can be of benefit to public organizations in such areas as EMS operations, rescue services, air-traffic control centers, road- and rail-traffic control centers, police and fire stations, and other public safety and security organizations. The reasons that call logging is used, the capabilities of the newest logging systems, systems integration, legal protection, monitoring and training, and reliability are discussed.